Pengaruh Penerapan Invitation Dialog pada Online Course - Zakharia, Elia (Jurnal Saintekom : Sains, Teknologi, Komputer dan Manajemen, 2017)
Invitation is a helpful hint, usually shown first when user open application or form. The form of invitation implementation is very diverse, and one of them is invitation dialog. The purpose of this study is to measure the effect of invitation dialog implementation on online course, in terms of usability (effectiveness and efficiency).Methods to achieve the purpose of this study consisted of five stages, namely requirement analysis of invitation dialog interface, design the interface, construct the prototype, usability testing and data collection, last data analysis and interpretation.Based on the test results from 32 Universitas Atma Jaya Yogyakarta (UAJY) students, implementation of invitation dialog affects the effectiveness of online course usage 93.75%, and efficiency 56.603%. Invitation dialog on the online course has a good effect on efficiency, but it does not have a significant impact on efficiency.